PENGARUH KOMPENSASI, MOTIVASI DAN KUALITAS KEHIDUPAN KERJA TERHADAP KINERJA KARYAWAN PADA PT. LIBERRO INDONESIA SURABAYA - Intan Lestari Hastuti; Kasmari Kasmari (Sekolah Tinggi Ilmu Ekonomi Dr Kh Ez Mutaqien, 2022)
This study aims to determine how the effects of compensation, motivation and quality of work life on the performance of employees PT. Liberro Indonesia Surabaya. The population in this study were all employees at PT. Liberro Indonesia Surabaya as many as 68 people. The sampling technique in this study used saturated sampling. The data collection method in this research is using a questionnaire and documentation. The number of respondents in this study were all employees of PT. Liberro Indonesia Surabaya as many as 68 people, but the returned questionnaires were 51 or 75%. The data analysis method used multiple linear regression analysis with IBM SPSS Statistics 25 program. The results of this study indicate that compensation, motivation and quality of work life simultaneously affect the performance of employees PT. Liberro Indonesia Surabaya. Then compensation partially has a negative and insignificant effect on employee performance, motivation has a positive and significant effect on employee performance, quality of work life has a positive and significant effect on employee performance.